Reward deficiency syndrome - Şahpolat, Musa; Arı, Mustafa; Kokaçya, Mehmet Hanifi; Çöpoğlu, Ümit Sertan (Journal of Dependence, 2014)
Reward deficiency syndrome (RDS) has been described as a statement resulted in many behavioral disorders due to chemical imbalances in the brain’s reward system. This system has been incidentally discovered by Olds in 1950. Limbic system is the basis of that system. It is now known that RDS is associated with a variety of disorders occur in a wide area of the brain covering the important parts of the limbic-system as basal ganglia, including the mesolimbic regions of the brain; particularly NAC, the prefrontal cortex, hypothalamus and amygdala. The limbic system, the basis for the perception of pleasure, controls basic emotions and behaviors. İt is stated that many neurotransmitters, especially dopamine play a role in the pathogenesis of RDS. Furthermore, it also controls important behaviors including memory and learning, sexual behavior, motivation and nutrition. It is reported that RDS has neurobiological common paths and relation with alcohol addiction, substance abuse, smoking, compulsive overeating, obesity, attention deficit and hyperactivity, Tourette’s disorder, uncontrolled internet usage and pathological gambling. RDS-related information and studies discussed in the literature were evaluated in this article.
Keywords: Reward deficiency syndrome; reward cascade; dependence